Breastfeeding self-efficacy among blind mothers - Sarah Angelo Dias; Thallyta Queiroz Silva; Dyego Oliveira Venâncio; Anne Fayma Lopes Chaves; Ana Carolina Maria Araújo Chagas Costa Lima; Mariana Gonçalves do Oliveira
ABSTRACT Objective: To evaluate breastfeeding self-efficacy among blind mothers. Method: This is a descriptive and exploratory research carried out in Fortaleza-Ceara, with ten blind mothers. Data were collected through an interview with the application of a socioeconomic and obstetric questionnaire and the Breastfeeding Self-Efficacy Scale - Short Form. Results: The majority of blind mothers presented high breastfeeding self-efficacy, but there were also mothers with low breastfeeding self-efficacy. Conclusion: It is necessary to follow-up mothers throughout the entire breastfeeding period to maintain or improve breastfeeding self-efficacy in this specific public.